‘Meisjes samen op reis is iets heel anders dan jongens’. Jeugdcruises en gender in de jaren 1930 - Van der Zande, Iris (TSEG - The Low Countries Journal of Social and Economic History, 2020)
In the 1930s, the first cruises that were exclusively organized for the youth – the so-called Tarakan and Slamat journeys – took place in the Netherlands. The Dutch youth, boys and girls separated, sailed to Norway, Scotland and England to spend a week-long holiday on board and ashore. Based on the writings of journalists, this article states that traveling in the 1930’s is presented as a masculine activity. The youth cruises were narrated around ideas about differences between boys and girls. By emphasizing this distinction, the journalists gave meaning to the journeys. The reporting on the journeys is characterized by various narratives that reflect an ambivalent attitude towards modernity and dominant gender ideas. This research aims to complement the history of youth tourism, in which travels in the early twentieth century are rare. Moreover, it underlines that tourism reflects dominant gender ideas and that gender and tourism are therefore intertwined.